Case reportImmune-complex deposits in “pauci-immune” glomerulonephritis: a case report and brief review of recent literature - El-Ters, Mireille; Muthyala, Umadevi; Philipneri, Marie D.; Hussein, Fadi A.; Lentine, Krista L. (Archives of Medical Science, 2010)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis is considered a “pauci-immune” disease, characterized by absent or mild glomerular tuft staining for immunoglobulin and/or complement. We describe a 72-year-old man with progressive renal failure over five months who was found to have P-ANCA associated crescentic glomerulonephritis. Renal biopsy also revealed immunofluorescence staining for Immunoglobulin G and C3. Treatment comprised corticosteroids, cyclophosphamide, and plasmapheresis but unfortunately kidney function did not recover, likely due to substantial interstitial fibrosis at diagnosis. This case illustrates that serologic evaluation for ANCAs should not be discounted when immune deposits are present. Prompt diagnosis is warranted.